The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-2141.2012.09077.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of homologous inositol hexaphosphate‐loaded red blood cells in sickle transgenic mice

Abstract: SummaryPatients with sickle cell disease (SCD) can present several severe symptoms during their lifetime, including painful events due to vascular occlusion (VOC). Even though multiple factors are involved in VOC, hypoxia is the most important triggering factor. Inositol hexaphosphate (IHP) reduces the oxygen-haemoglobin affinity thus improving the oxygen release in the blood stream and in the tissues. Thus, IHP-loaded homologous red blood cells (IHP-RBCs) could be able to reduce disorders in SCD. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As an example by Rossi et al in 2014, the use of Annexin V probe on murine RBC confirmed that damage is limited to 4.9% of total loaded cells, implying that 95.1% have normal surface characteristics and would have a normal survival in circulation . These data are corroborated by the half‐life of loaded murine RBC that has been repeatedly reported to be in the range of 6–11 days, slightly reduced in comparison with native cells (range 12–14 days), due to a minimal loading‐induced damage. Furthermore, the in vivo survival results of human carrier erythrocytes reported by Bax et al (1999), assessed by monitoring the disappearance of 51 Cr label from circulation of unloaded erythrocytes (cells submitted to a loading procedure without the addition of cargo), demonstrate that RBC engineering should be performed without altering the normal mean cell life and cell half‐life of the carrier RBC (89–131 and 19–29 days, respectively) .…”
Section: Biocompatibility Of Carrier Rbc and Potential Challengesmentioning
confidence: 73%
“…As an example by Rossi et al in 2014, the use of Annexin V probe on murine RBC confirmed that damage is limited to 4.9% of total loaded cells, implying that 95.1% have normal surface characteristics and would have a normal survival in circulation . These data are corroborated by the half‐life of loaded murine RBC that has been repeatedly reported to be in the range of 6–11 days, slightly reduced in comparison with native cells (range 12–14 days), due to a minimal loading‐induced damage. Furthermore, the in vivo survival results of human carrier erythrocytes reported by Bax et al (1999), assessed by monitoring the disappearance of 51 Cr label from circulation of unloaded erythrocytes (cells submitted to a loading procedure without the addition of cargo), demonstrate that RBC engineering should be performed without altering the normal mean cell life and cell half‐life of the carrier RBC (89–131 and 19–29 days, respectively) .…”
Section: Biocompatibility Of Carrier Rbc and Potential Challengesmentioning
confidence: 73%
“…Figure 4 shows micrographs of erythrocyte samples before and after the loading procedure by , have been reported to be for human RBCs within the normal ranges, being about 110 days and 28 days, respectively (normal values: MCL 89-131 days, MHL 19-29 days) (Bax et al 1999). Treated murine RBCs show a slightly reduced MHL (6-11 days vs normal 12-14 days) (Magnani et al 1990;Bourgeaux et al 2012). The dialysis method to develop proteinloaded erythrocytes has been employed in several in vitro (Magnani et al 1988) and in vivo preclinical and clinical studies (Bax et al 2013;Bax et al 2007).…”
Section: Loading Proceduresmentioning
confidence: 82%
“…Indeed, under hypotonic conditions pores till to 500 Å open on the erythrocyte membrane, permitting the entrance of one or more proteins, and by restoring physiological osmotic conditions, the membranes reseal and RBCs reassume their normal biconcave shape and impermeability features. Once in circulation, resealed RBCs show an almost normal survival times as demonstrated by the half-life values both of murine [2,3] and human [4,5] loaded RBCs. Another potential developing technology is based on the manufacture of red blood cells expressing bio-therapeutic proteins to create highly selective and allogeneic cellular medicines aimed at treating a range of diseases by the hematopoietic stem cell therapy [www.rubiustx.com].…”
Section: Introductionmentioning
confidence: 95%